Urban planning and development act, 1973 Uttar Pradesh: as amended by act no. 1 of 2008 - Mukherjee, S. (Allahabad Allahabad law emporium, 2023)
Uttar Pradesh Urban planning and development act
Keywords: Uttar Pradesh development act